Corrosion protection of carbon steel by tetraphosphonates of systematically different molecular size. (December 2018) - Moschona, Argyri; Plesu, Nicoleta; Mezei, Gellert; Thomas, Andrew G.; Demadis, Konstantinos D.
Graphical abstract: Highlights: A family of systematically elongated tetraphosphonate corrosion inhibitors is studied by XPS. The tetraphosphonates stringly interact with the mild steel surfaces at pH 3. Shorter chain lengths on the inhibitor backbone cause surface dissolution. Abstract: We study the interaction of six systematically varied tetraphosphonate molecules with carbon steel surfaces by XPS at pH 3. All tetraphosphonates [EDTMP (C2), TDTMP (C4), HDTMP (C6), ODTMP (C8) and DDTMP (C12)] belong to the aminomethylene-phosphonate family, and they possess systematically elongated backbone (from two to twelve methylene groups separating the N atoms). XPS studies were performed on powdered samples and also on immersed carbon steel specimens in aqueous solutions. The XPS results also suggest that the tetraphosphonic acid molecules become significantly deprotonated upon interaction with the carbon steel surface and that the surface interaction of the tetraphosphonic acid family leads to additive adsorption on the steel surface via the phosphonate groups. The mode of corrosion inhibition was studied by potentiodynamic polarization and electrochemical impedance spectroscopy. The changes observed in the impedance parameters, like charge transfer resistance (Rct ) and constant phase element (CPE) confirm the strong adsorption on the metal surface. The nature of the protective layer formed on the carbon steel surface was examined by Attenuated Total Reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy and optical microscopy.